1994
DOI: 10.1111/j.1360-0443.1994.tb03309.x
|View full text |Cite
|
Sign up to set email alerts
|

Death and survival in a cohort of heroin addicts from London clinics: a 22‐year follow‐up study

Abstract: Data are presented on the 43 people who died over a 22-year follow-up period of a cohort of 128 heroin addicts drawn in 1969 from the newly opened London clinics. The main causes of death were drug-related, with 18 deaths specifically determined as due to overdose, of which the great majority were among people being prescribed opiates at the time. The mortality rate was a mean of 1.84% annually, and the excess mortality ratio was 11.9. This excess was highest at the beginning and varied over the period of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
133
3
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(156 citation statements)
references
References 18 publications
(27 reference statements)
13
133
3
7
Order By: Relevance
“…Our findings support the acknowledged link between age and the likelihood of OD death 1,12,13,15 in the U.S. and other wealthy societies. Chicago_s mean age of death-39 years-resonates with the findings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings support the acknowledged link between age and the likelihood of OD death 1,12,13,15 in the U.S. and other wealthy societies. Chicago_s mean age of death-39 years-resonates with the findings.…”
Section: Discussionsupporting
confidence: 85%
“…Although OD incidence varies across settings, annual mortality rates among untreated opiate addicts range from 1 to 2% with higher mortality incidence in some populations. [12][13][14][15][16] International OD death rates among opiate users range from six to 20 times greater than the norm for their drug-free peers, with accidental OD accounting for up to 45% of their deaths. 17,18 Intravenous heroin use-as opposed to less lethal routes of administration such as intranasal ingestion-accounts for the vast majority of opiate-related ODs.…”
Section: Introductionmentioning
confidence: 99%
“…37 Heroin as primary drug of choice is a major focus in the addiction mortality literature because of the high risk of overdose and infectious disease associated with its use. 4,15,17,18,40,41 Homelessness is another predictor of risk of death for substance-dependent people. [19][20][21] Of note, any homelessness was not a significant risk factor in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…9,15,16 Much of the mortality research including people with substance dependence has focused on injection drug users, primarily of heroin. 15,17,18 This is likely because of the high prevalence of overdose, among other serious medical consequences, and the concomitant risk of death. 4 More than two-thirds of illicit drug users in an Australian study reported nonfatal drug overdose in their lifetime, 17 and a substantial proportion of the excess mortality in drug users is because of drug overdose.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although depressive symptoms are strong predictors of suicide and attempted suicide, 6,7 most drug overdoses do not appear to be suicide attempts. [8][9][10] It has been hypothesized that some individuals use illicit drugs to selfmedicate for dysphoria and other mental conditions. 11 Depressed drug users are more likely to use more of their drug to alleviate their symptoms and improve their mood.…”
Section: Introductionmentioning
confidence: 99%